Clinical Impact of Local Anesthesia on Sedation Stability and Propofol Dosage in Pediatric Dental Sedation - Merve Hayriye Kocaoglu; Çağıl Vural; Betül Büşra Ursavaş (European Annals of Dental Sciences)

(untitled)
Background: Local anesthesia (LA) is often preferred for stabilization of vital signs, depth of anesthesia and pain control in dental restorations but the efficacy of LA administration during deep sedation is controversial.Aim: To retrospectively investigate the effects of LA on heart rate, blood pressure, oxygen saturation, depth of anesthesia and total dose of anesthetic drugs given in pediatric patients sedated for dental procedures.Materials & Methods: Records of 50 healthy children were divided into two groups: Patients who received infiltration LA at the beginning of sedation (Early LA) or who received LA at the end of sedation after completion of restorations (Late LA). Demographic data, hemodynamic data, Bispectral Index (BIS) scores, Ramsey Sedation Scale scores, total propofol dose administered were compared. Since the difference between two quantitative dependent variables did not meet the assumptions of normal distribution, Wilcoxon Signed Rank test was used. Generalized Estimation Models were used to look at the effect of quantitative variables with repeated measures (BIS and Ramsey) on groups.Results: There was no statistically significant difference between the groups in terms vital signs, depth of anesthesia (BIS (p=0.190) and Ramsey score (p=0.887)), and total propofol dose adjusted for BMI (p=0.59). Conclusion: The presence of LA during deep dental sedation has no significant impact on vital signs, depth of anesthesia and total amount of propofol used compared to the absence of LA. LA does not contribute to stabilization of dental sedation, but close monitoring of deep sedation prevents drug overdose.